Patterns of Antiepileptic Drug Reactions in Children: A Multicenter Study: Antiepileptic Drug Reactions in Children - sedighi, parinaz; Khalili, Neda; Khalili, Nastaran; Doosti-Irani, Amin; Moradi, Atefeh; Moghadam, Samira; Nemati, Meshkat; Mohammadi Jorjafki, Sobhan; Badv, Reza Shervin; Sedighi, Iraj (Iranian Journal of Child Neurology, 2022)
Objectives Antiepileptic drugs are among the most common triggers of cutaneous adverse reactions. About 5–17% of epileptic patients develop idiosyncratic skin reactions at some point during their treatment course, most of which occur within the first two months of drug initiation. This study aimed to investigate the pattern of cutaneous drug reactions associated with anticonvulsant use among the pediatric population in Iran to identify high-risk individuals. Materials & Methods In this retrospective descriptive study, medical records of children aged two months to 14 years, who were diagnosed with drug reactions due to anticonvulsant drugs between April 2007 and March 2018, were reviewed, and relevant information were extracted. This multicenter study was conducted in several provinces of Iran. Results A total of 186 cases with a final diagnosis of the antiepileptic druginduced eruption were evaluated. The median age of participants was 36 months (range: 2-168), and 56% were male. In approximately 70% of the children, phenobarbital was the culprit. The median time interval between initiation of the causative drug and development of rash and fever was 10 and 7 days, respectively. The most common rash type was maculopapular rash (69%). Overall, 33% of the patients only received antihistamines after discontinuation of the causative drug. Conclusion Similar to previously published studies in Iran, phenobarbital was the main cause of cutaneous drug reactions to antiepileptic drugs, indicating the necessity of paying more attention when prescribing phenobarbital for Iranian pediatrics.